2012
DOI: 10.1021/jo300812q
|View full text |Cite
|
Sign up to set email alerts
|

Transannular Diels–Alder Reactivities of 14-Membered Macrocylic Trienes and Their Relationship with the Conformational Preferences of the Reactants: A Combined Quantum Chemical and Molecular Dynamics Study

Abstract: Transannular Diels-Alder (TADA) reactions that occur between the diene and dienophile moieties located on a single macrocyclic triene molecule have been recognized as effective synthetic routes toward realizing complex tricyclic molecules in a single step. In this paper, we report a comprehensive study on the TADA reactions of 14-membered cyclic triene macrocycles to yield A.B.C[6.6.6] tricycles using quantum chemical methods and using classical molecular dynamics simulations. A benchmark study has been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The increase of molecular complexity led to a more pronounced asynchrony of the C-C bonds formation. The result is in a good agreement with the earlier DFT calculations of the [4+2] transition states [ 41 , 42 , 43 , 44 , 45 , 46 , 83 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The increase of molecular complexity led to a more pronounced asynchrony of the C-C bonds formation. The result is in a good agreement with the earlier DFT calculations of the [4+2] transition states [ 41 , 42 , 43 , 44 , 45 , 46 , 83 ].…”
Section: Resultssupporting
confidence: 91%
“…DFT methods were proven to provide reliable and accurate results for the correct description of different types of cycloaddition reactions, in particular the [4+2] cycloaddition [ 61 , 62 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] and its transannular variant, implemented in the synthesis of Spinosyn A [ 83 ]. Reaction ( a ) was investigated in several previous studies (see refs.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the reaction to form up to four stereogenic centers with predictable regiochemistry and absolute configuration, [3] combined with the ease of operation and convenient execution of chiral auxilaries [4] and catalysts [5] have facilitated successful applications of this pericyclic process in stereoselective synthesis of enantioenriched natural products, [6] biologically active compounds, [7] and desired complex molecular structures [8] . Employment of high pressure techniques [9] and Lewis acid mediated methods [10] along with the development of intramolecular, [11] transannular, [12] temporary tethered, [13] self‐assembled, [14] and hetero [15] variants of the reaction have further extended the scope of this remarkable process.…”
Section: Introductionmentioning
confidence: 99%
“…The structures from the trajectories of the REMD simulations on all six systems were grouped based on their conformations using a clustering method proposed in our recent study. 49 The dihedral angles involving the carbon atoms in the ring systems were calculated for all the structures in the trajectories. Based on a dihedral bin size of 30u, multi-dimensional histograms were generated: 552, 562, 662, 572, 672 and 772 ring systems have 12, 13, 14, 14, 15 and 16 dihedrals respectively.…”
Section: Structures and Stabilities Of The Trienesmentioning
confidence: 99%
“…The conformational properties of these trienes were investigated using MD simulations and it was found that these properties play a major role in determining the TADA reactivity. 49 In the present paper, the effect of -CH 2 -linker length between the diene and the dienophile of the macrocyclic ring on TADA reactivity, and the conformational preferences of the reactants are investigated. The number of -CH 2 -linkers were varied from three to five resulting in six different sets of macrocyclic trienes, which are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%